Study on the Capacity of Auxiliary Weir-Type Spillway at Bulango Ulu Dam Gorontalo Province Using Spillway Routing - Miskar Maini; Furqan Ali Yusuf (G-Tech: Jurnal Teknologi Terapan, 2025)
The spillway on the dam functions as a safeguard against the dangers of flood water, which overflows gradually to prevent overtopping. The estimated design of flood discharge uses the SCS SUH method, while outflow discharge is calculated through spillway routing based on reservoir storage characteristics. The study results show that the maximum flood discharge with a return period of 2 years up to the Probable Maximum Flood (PMF) scenario is 420.26 m³/s to 2,288.05 m³/s respectively. Spillway routing is carried out to drain flood water from the reservoir, with a maximum outflow discharge of 44.4 m³/s to 1,250.5 m³/s, according to the flood return period. This reservoir is able to reduce flooding significantly, with a flood reduction of 89.4% at a return period of 2 years and 45.3% for PMF. The water level at the spillway was measured at various return periods, indicating there was no overtopping until the PMF flood event. Bulango Ulu Dam, which is designed with a top Dam elevation of +105 m, can safely withstand PMF flood discharge.